2022
DOI: 10.1002/vms3.993
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Moringa leaf flavonoids on the production performance, immune system, and rumen fermentation of dairy cows

Abstract: Background Unreasonable use of antibiotics in animals is a major concern and will remain so, thus affecting people's health. However, the application of plant extracts can better solve this problem. Objectives The purpose of this study was to study the effect of Moringa leaf flavonoids on the production performance, immunity, and rumen fermentation of dairy cows. Methods Nine Holstein multiparous cows (average weight: 550 kg; days of lactation: 150 ± 6 days) were used in the experiment, using a 3 × 3 Latin squ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 32 publications
(37 reference statements)
0
1
0
Order By: Relevance
“…Furthermore, A recent study showed that condensed tannins from grapeseed induced slight change in microbial structural lipids, which decreased the level of cis-9, cis-12 C18:2 and increased the levels of cis-9, trans-11 C18:2 and trans-11 C18:1 in vitro (Costa et al, 2017). According to Liu et al (2022), including Moringa leaf flavonoids in the diet can boost the protein content in milk. Similarly, Zhao et al (2022a) discovered that adding citrus peel extract to milk can decrease SFA and increase MUFA and CLA due to its high flavonoid content.…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, A recent study showed that condensed tannins from grapeseed induced slight change in microbial structural lipids, which decreased the level of cis-9, cis-12 C18:2 and increased the levels of cis-9, trans-11 C18:2 and trans-11 C18:1 in vitro (Costa et al, 2017). According to Liu et al (2022), including Moringa leaf flavonoids in the diet can boost the protein content in milk. Similarly, Zhao et al (2022a) discovered that adding citrus peel extract to milk can decrease SFA and increase MUFA and CLA due to its high flavonoid content.…”
Section: Introductionmentioning
confidence: 99%